Patterns of regulatory behavior in the still-face paradigm at 3 months : a comparison of Brazilian and Portuguese infants - Fuertes, Marina (2021)
Copyright: © 2021 Fuertes et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.